El anuncio de pruebas en la demanda de alimentos y la vulneración de los derechos constitucionales del alimentado - Cuenca Calderon, Jorge Fernando (2014)
The present research on the theme: The announcement of evidence in food demand and the violation of the constitutional rights of the fed, is a current topic of daily living in trials to provide food. So the overall goal is to get through reform to subsection 34 3RD Art of Title V , the right to food of the Law Amending the Code of Children and Adolescents , the announcement of test in the same conditions for parts , and so to realize the full enjoyment of constitutional rights , while the hypothesis states that the amendment to the 3rd paragraph of Article Article 34 of the Code of Children and Adolescents in terms of ad testing, ensure constitutional rights. This work will benefit the plaintiffs submit judgments by providing food , allowed to present evidence on equal terms , for which you must present this proposal to amend the National Assembly , because it is the competent body to give the corresponding procedure . In the theoretical framework data known authors who express their views about the test conditions in which they are presented, equity rights and constitutional rights are cited. The development of the proposed amendment to the 3rd paragraph of Art Article 34, Title V, of the right to food of the Law Amending the Code on Children and Adolescents, is performed based on the outline provided by State Technical University Queued.